Allogeneic Antigen Composition for Preparing Universal Cancer Vaccines - Petr G. Lokhov; Elena E. Balashova (Journal of Immunology Research)
Recently it was demonstrated that tumors induce specific changes to the surface of human endothelial cells thereby providing the basis for designing endothelial cell-based vaccines that directly target antigens expressed by the tumor endothelium. The present report extends these studies in vitro by investigating the efficacy of allogeneic antigens with regard to their ability to target immune responses against the tumor vasculature since alloantigens simplify vaccine development and implementation in clinical practice. We demonstrated that allogeneic SANTAVAC (Set of All Natural Target Antigens for Vaccination Against Cancer), which presents a specifically prepared composition of cell surface antigens from tumor-stimulated endothelial cells, allows targeting of the tumor vasculature with efficacy of 17, where efficacy represents the killing rate of target cells before normal cells are adversely affected, and efficacy of 60, where efficacy represents the fold decrease in the number of target cells and directly relates to tumor growth arrest. These data suggest that allogeneic SANTAVAC may be considered an antigenic composition that following administration in the presence of respective adjuvants may be clinically tested as a therapeutic or prophylactic universal cancer vaccine without adverse side effects to the normal vasculature.